Pemanfaatan Yogurt Untuk Menurunkan Tekanan Darah Pada Ibu Hamil Hipertensi - Anggun Rizka Saputri; Linda Yanti; Arlyana Hikmanti (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Someone who suffers from hypertension during pregnancy can cause preeclampsia. Someone who has preeclampsia has a risk of having seizures to produce foam. The prevalence of pregnant women with hypertension is 16% in Central Java. The purpose of this study was to determine the effectiveness of yogurt in reducing high blood pressure in pregnant women with hypertension. Case study is the method used in this research. The subjects were pregnant women with hypertension in the second and third trimesters. This community service experimented with 130 ml of yogurt a day for 14 days on pregnant women with hypertension and blood pressure measurements were taken every day. From the community service given to pregnant women with hypertension for 14 days it has the effect of lowering blood pressure every day.